2020
DOI: 10.1002/adfm.202000829
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Nonlinear Optical Selection Rules in Metallic Quantum Wells

Abstract: Intersubband transitions (ISBTs) in conduction-band quantum wells (QWs) have attracted tremendous attention for their high technological potential, ranging from quantum cascade lasers, quantum well infrared photodetectors, to various nonlinear optical elements. One of the main characteristics of using the ISBTs is their polarization selection rule, which forbids a normalincidence geometry. Here, it is shown that the ISBT selection rule is not strict on optical nonlinearities in metallic QWs (MQWs). The nonline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The metalens relies on the resonators‐on‐a‐mirror structure to tailor a phase profile and form an image of an object in its reflection mode. Because the TiN quantum wells possess giant Kerr nonlinearity, [ 38 ] the optical constants of the TiN/Al 2 O 3 multilayers and thus the resultant phase of the metalens becomes tunable with respect to the local illumination intensity. Therefore, this nonlinear metalens acts as not only an imaging element but also an image processing element, which transforms the image by superimposing an additional phase profile defined by the intensity distribution in space.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metalens relies on the resonators‐on‐a‐mirror structure to tailor a phase profile and form an image of an object in its reflection mode. Because the TiN quantum wells possess giant Kerr nonlinearity, [ 38 ] the optical constants of the TiN/Al 2 O 3 multilayers and thus the resultant phase of the metalens becomes tunable with respect to the local illumination intensity. Therefore, this nonlinear metalens acts as not only an imaging element but also an image processing element, which transforms the image by superimposing an additional phase profile defined by the intensity distribution in space.…”
Section: Resultsmentioning
confidence: 99%
“…[ 41 ] The giant Kerr‐type nonlinearity in metallic quantum well system mainly stems from the intersubband transition and can be aligned at the desired wavelength by tuning the quantum well thickness. [ 38 ] In this work, 2.4 nm TiN quantum wells are chosen for the computational metalens, enabling intersubband transition enhanced giant Kerr nonlinearity with working wavelength also around 800 nm. The Z‐Scan experiment for the nonlinear property is described in Supporting information, Section S3.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been shown that ultrathin metallic quantum well possesses exceptionally large nonlinearity at visible to near-IR frequency range. A nonlinear metasurface based on such material system will revolutionize the field of tunable computational metasurface, laying the cornerstone for nonlinear optical computations [177][178][179].…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…3 Anomalous nonlinear optical selection rules that are very useful for many nonlinear optical elements have been observed in metallic quantum wells with an ultrathin plasmonic TiN layer sandwiched by Al 2 O 3 layers. 4 To construct single-crystalline rock-salt TMNs/metal−oxide heterostructures with superior performance, the lattice mismatch between these two functional layers is a nonneglectable factor. The difficulty of fabricating single-crystalline heterostructures with a lattice mismatch of over 5% can hinder the epitaxial integration of rock-salt TMNs with many functional oxides that span a wide spectrum of lattice mismatch.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, unexpected emergent interfacial room-temperature ferromagnetism has been found in CrN/Cr 2 O 3 superlattices . Anomalous nonlinear optical selection rules that are very useful for many nonlinear optical elements have been observed in metallic quantum wells with an ultrathin plasmonic TiN layer sandwiched by Al 2 O 3 layers …”
Section: Introductionmentioning
confidence: 99%